2011
DOI: 10.1007/s00421-011-2108-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males

Abstract: The purpose of this study was to investigate whether different modes of single-bout exercise would cause different responses in short-term bone metabolism. 24 untrained male college students (19.1 ± 0.1 years old) were recruited and randomly assigned to three groups: (1) a single-bout plyometric exercise group (the PL group, n = 8), (2) a 200-meter × 10 intermittent running group (the IR group, n = 8) and (3) a sedentary control group, which followed the same time schedule of experimentation without performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…This is consistent with Lin et al (2012), who reported no change in TRAP5b, a marker of bone resorption, following plyometric exercise in men. Rogers et al (2011), on the other hand, reported a decrease in TRAP5b post-exercise.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with Lin et al (2012), who reported no change in TRAP5b, a marker of bone resorption, following plyometric exercise in men. Rogers et al (2011), on the other hand, reported a decrease in TRAP5b post-exercise.…”
Section: Discussionsupporting
confidence: 93%
“…Nonweight-bearing exercise, such as cycling, does not appear to result in a clear pattern of changes of biochemical markers of bone turnover (Guillemant et al 2004;Herrmann et al 2007;Pomerants et al 2008). Two studies examined the effect of high-impact, plyometric exercise (jumping) on markers of bone turnover in men and report inconsistent results: Rogers et al (2011) reported no change in markers of bone formation (osteocalcin and bone ALP) and transient changes in markers of bone resorption (TRAP5b and CTx), while Lin et al (2012) demonstrated an acute increase in osteocalcin and no change in TRAP5b in men.…”
Section: Introductionmentioning
confidence: 96%
“…(9) The bonederived protein, osteocalcin, for example, has been reported to act on muscle cells to mediate the response to exercise. (41,42) In observational studies, osteocalcin levels increase following exercise (43)(44)(45)(46) and are positively correlated with muscle strength. (47) Therefore, it is possible that bone-derived signals, such as osteocalcin, are directly contributing to the increased risk of BADL disability and future work is necessary to determine whether osteocalcin serves as a mechanistic link connecting bone and disability.…”
Section: Discussionmentioning
confidence: 99%
“…This type of exercise has been shown to be an effective method for increasing lean mass in adolescents with Down syndrome, 17 and as bone mass is closely associated with lean mass this is a positive finding. It has also been suggested that in young people the mechanical impact resulting from plyometric exercise is one of the most osteogenic activities, 12 and could enhance the levels of osteocalcin, 18 which is an established and extensively used biochemical marker of bone formation 19 …”
mentioning
confidence: 99%